Pengaruh Bauran Promosi Terhadap Minat Partisipasi Masyarakat Pada Event-Event Tahunan Di Solo - Mutmainah, Siti; , Drs. M. Farid Wajdi, Ph.D (2016)
This research aims to analyze the influence of promotion mix on people's interest in annual events in Solo. This research involves totally 60 respondents, in which they are Solo citizens. The primary data is obtained through questionnaires method. Hereinafter, it utilizes hypothesis test, multiple linear regressions, t test, and F test. The outcomes of this research shows that partially, the promotion mix including advertising, personal selling, marketing promotion, and publication significantly influence on participation interest in the annual events in Solo. Simultaneously, the advertising, personal selling, marketing promotion, and publication also influence people's interest to participate annual events in Solo significantly. The four variables bear totally 48.8% on the people's interest to participate annual events in Solo, while the other 51.2% influenced by the other factors. Keywords : Promotion Mix (Advertising, Personal Selling, Sales Promotion, and Publicity), Minat Interest Participation